Interleukin-6 and Neutrophil–Lymphocyte Ratio in Predicting Outcome of Confirmed COVID-19 Patients - Harsini Harsini; Jatu Aphridasari; Artrien Adhiputri; Hie Sukiyanto; Aditya Sri Listyoko; Agung Prasetyo (Jurnal Respirasi, 2023)
Introduction: COVID-19 emerged as a pandemic about 2 years ago. Severe and critical COVID-19 has been associated with increased interleukin 6 (IL-6) level and neutrophil–lymphocyte ratio (NLR). This study aimed to test whether IL-6 and/or NLR are associated with COVID-19 mortality. Methods: Subjects were COVID-19 patients with suspected Omicron variant infection that were hospitalized at Dr. Moewardi Hospital from October 2021 to March 2022. According to their medical records, subjects were divided into survivor and non-survivor groups. Serum level of IL-6 and NLR at admission were recorded, compared, and analyzed for association with mortality. Results: Seventy-four respondents, average age 53.07 ± 16.2 years, joined the research. The area under curve (AUC) value of IL-6 was 0.740, with a cut-off value of 42.00 mg/dL (73.9% sensitivity; 70.6% specificity). The AUC value of NLR was 0.721, with a cut-off value of 5.51 (73.9% sensitivity; 60.8% specificity). IL-6 had a higher odds ratio than NLR as a risk factor for mortality (6.80 [95% CI 2.24–20.61; p < 0.001]; 4.39 [95% CI 1.48–13.03; p < 0.001], respectively). The correlation between IL-6 and NLR had an r-value of 0.164 (p = 0.164). Conclusion: There was no difference in sensitivity between IL-6 level and NLR as mortality predictors of COVID-19, but serum IL-6 level was more specific. IL-6 level correlated positively with NLR, but there was no significance.